The law of bankers' commercial credits - Gutteridge, Harold Cooke; Megrah, Maurice (London : Europa Publications, 1968)
This edition differs materially from the last. There have existed since 1933 a body of rules entitled the Uniform Customs and Practice for Documentary Credits, formulated by the International Chamber of Commerce. Since July, 1963, the Uniform Customs have been applied by almost all banks in the world, with the result that since that time they have been made part and parcel of virtually every credit issued. Thus the contract embodied in the documentary credit must be construed in the light of the Uniform Customs and the reason for the opening sentence to this introduction becomes obvious.
Includes bibliographical references and index.
ne 03/10/2019
Loans
Keywords: Letters of credit; Documentary credit--Law and legislation; Great Britain